Supervision of Economics Programme in Post-Basic Education and Career Development (PBECD) in Nigeria - Ogunode, Niyi Jacob; Tanimola, FABIYI, Olawale (Researchparks Publishing, 2023)
This paper examined the challenges militating against effective supervision of the Economics Programme in Post-Basic Education and Career Development (PBECD) in Nigeria. Secondary data were used to provide empirical support for the paper. Data were collected from both print materials and online publications. The paper identified inadequate funding, shortage of supervision materials, inadequate transport facilities, poor communication skills, shortage of Economics Supervisors, poor human relations skills, insecurity and poor capacity development as problems hindering effective supervision of the Economics Programme in Post-Basic Education and Career Development (PBECD) in Nigeria. The paper recommended the following: Increment in the funding of Economics supervision in the Post-Basic Education and Career Development (PBECD) in Nigeria.